Field Monitoring-Based and Theoretical Analysis of Baota Mountain Landslide Stability - Yaming Tang; Heping Shu; Qiang Xue; Jiayun Wang; Wei Feng; Hongna Ma; Yan’e Li; Jin Luo; Hamid Reza Pourghasemi (Advances in Civil Engineering)
Landslide is one of the most widely distributed surface morphological landscapes, and it can cause a series of major economic and human losses. Field monitoring and limit equilibrium methods were applied to investigate Baota Mountain landslide stability, and soil volumetric water content, different scales of rainfall data, and landslide displacements were monitored using various equipment. The theoretical factor of safety was also calculated for the landslide. Finally, the theoretical results were validated by monitoring data in the field. The results demonstrate that soil volumetric water content experienced the greatest change with time at a depth of 0.2 m and then 1 m; however, the change in soil volumetric water content was relatively small with time at a soil depth ranging from 2.0 m to 4.0 m. Soil volumetric water content also did not change with time at a soil depth of 5.0 m and below. In addition, the retardation effect was found in different depths of volumetric water content for continuous rainfall. The safety factors were 2.713 and 1.133 for landslide No. 1 and landslide No. 2, respectively. These results indicate that landslide No. 1 is relatively stable, but there is a probability of the occurrence of movement in landslide No. 2. The monitoring displacement data indicate that landslide No.1 was in a relatively stable state between 2008 and 2013, and this result was in accordance with the value of theoretical calculation. This study provided relevant parameters for numerical simulation of landslides in loess areas.